Conceptualising a new and contemporary model for the successful implementation of "continuous" budgeting / Wee Shu Hui, Ibrahim Abdul Rahman and Syazliana Kassim - Wee, Shu Hui; Abdul Rahman, Ibrahim; Kassim, Syazliana (Research Management Institute (RMI), 2013)
Budgets have been the most important management control and tool for decades. Budgets are being used to give direction to company by setting the predetermined targets to be achieved. Company used budgeting in setting the rewards, plan actions, allocate resources, coordinate plans across the company, and then measure and control performance against the agreed plan. However, as time pass by, the management and control tools also have evolved. There has been an increasing dissatisfaction with the budgeting practices that was developed in the 1920's where things were not unpredictability like todays. In the present days, we have an environment where the competitive factor between the companies have grown. The increasing complexity in business has made the future more unpredictable. This new environment gives new challenges for a company to control their management. Budgeting models should be able to drive the companies to be in line with the developments of today's business markets that growing to be fast moving and competitive. Aware of the rapidly growing competition, companies have evaluating their budgeting systems. From the evaluating process, there are some companies that are dissatisfied with their budgeting systems. Hence, many companies tried to improve their budgeting systems (Libby & Lindsay, 2010). Additionally, in coping the increasing complexity environment, there is new management and control tools have been developed. One example is the beyond budgeting model. Beyond budgeting is a model that suggests the abolishment of annual budgets and implements tools that are better in managing the company than traditional annual budgets.